If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(u + 1) + y = 3(u + -1) + 7 Reorder the terms: 5(1 + u) + y = 3(u + -1) + 7 (1 * 5 + u * 5) + y = 3(u + -1) + 7 (5 + 5u) + y = 3(u + -1) + 7 Reorder the terms: 5 + 5u + y = 3(-1 + u) + 7 5 + 5u + y = (-1 * 3 + u * 3) + 7 5 + 5u + y = (-3 + 3u) + 7 Reorder the terms: 5 + 5u + y = -3 + 7 + 3u Combine like terms: -3 + 7 = 4 5 + 5u + y = 4 + 3u Solving 5 + 5u + y = 4 + 3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3u' to each side of the equation. 5 + 5u + -3u + y = 4 + 3u + -3u Combine like terms: 5u + -3u = 2u 5 + 2u + y = 4 + 3u + -3u Combine like terms: 3u + -3u = 0 5 + 2u + y = 4 + 0 5 + 2u + y = 4 Add '-5' to each side of the equation. 5 + 2u + -5 + y = 4 + -5 Reorder the terms: 5 + -5 + 2u + y = 4 + -5 Combine like terms: 5 + -5 = 0 0 + 2u + y = 4 + -5 2u + y = 4 + -5 Combine like terms: 4 + -5 = -1 2u + y = -1 Add '-1y' to each side of the equation. 2u + y + -1y = -1 + -1y Combine like terms: y + -1y = 0 2u + 0 = -1 + -1y 2u = -1 + -1y Divide each side by '2'. u = -0.5 + -0.5y Simplifying u = -0.5 + -0.5y
| 4/x=24 | | k=6r-s | | x-.25x=45 | | -27/2 | | 660x/t^2 | | 0=(121x^2+242x)(-242x-4) | | n/14=-10 | | 2(3+0.8x)=1.6x+6 | | 32p^2-8p-180=0 | | (5x)/4=5/x | | (2k-3)/3 | | 0.6/0.12 | | f(x)=(2x^2)+1 | | 2k-3/3 | | 8n-3n=4n-7 | | (5x)x(x)= | | 13x-(5x+7)+32=3x | | w^2+4w-35=0 | | 34=b+13 | | 21=z-9 | | (-5x+3)-(-7x-1)= | | 9n^2+31n+12=0 | | (7a/30)÷1/30 | | 18/22.50 | | 4/9x3 | | 7a/30÷1/30 | | -7.9-3y-2.2-y=-3y-2.7 | | -61=-8p+3 | | 25.50+6w=45 | | H=16t(6-t) | | 3(8+c)=2(c-7) | | 10x+7=6x+7 |